Impact of demographic transformation on future rice farming in Asia - Bhandari, Humnath; Mishra, Ashok Kumar (SAGE Publications, 2018)
We examine the depth and breadth of ongoing demographic transformation in Asia and draw ramifications on future rice farming using long-run time-series data from 17 major rice-growing countries in Asia. We found that Asia is undergoing declining trends in women fertility, child mortality, family size, population growth, the proportion of the agricultural population, and involvement of youth in agriculture. On the other hand, rural out-migration, aging of the farming population, and urbanization show increasing trends. These emerging trends will have far-reaching impacts on future rice farming mediated through labor market, rice market, rice demand, and rice supply. Policymakers and scientists must anticipate more rapid demographic transformation in the future and implement necessary technological, institutional, policy, and strategic solutions to manage or cope with future demographic transformation.